Measuring Water Distribution in the Heart: Preventing Edema Reduces Ischemia–Reperfusion Injury. Issue 12 (17th December 2016) - Andrés‐Villarreal, Mireia; Barba, Ignasi; Poncelas, Marcos; Inserte, Javier; Rodriguez‐Palomares, José; Pineda, Victor; Garcia‐Dorado, David
Abstract : Background: Edema is present in many heart diseases, and differentiation between intracellular (ICW) and extracellular (ECW) myocardial water compartments would be clinically relevant. In this work we developed a magnetic resonance imaging–based method to differentiate ICW and ECW and applied it to analyze ischemia–reperfusion–induced edema. Methods and Results: Isolated rat hearts were perfused with gadolinium chelates as a marker of extracellular space. Total water content was measured by desiccation. Gadolinium quantification provided ECW, and ICW was calculated by subtraction of ECW from total water content. In separate experiments, T1, T2, diffusion‐weighted imaging and proton‐density parameters were measured in isolated saline‐perfused hearts. In in‐situ rat hearts, ECW and ICW were 79±10 mL and 257±8 mL of water per 100 g of dry tissue, respectively. After perfusion for 40 minutes, ECW increased by 92.4±3% without modifying ICW (−1±3%). Hyposmotic buffer (248 mOsm/L) increased ICW by 16.7±2%, while hyperosmotic perfusion (409 mOsm/L) reduced ICW by 26.5±3%. Preclinical imaging showed good correlation between T2 and diffusion‐weighted imaging with ECW, and proton‐density correlated with total water content. Ischemia–reperfusion resulted in marked myocardial edema at the expense of ECW, because of cellular membrane rupture. When cell death was prevented by blebbistatin, water content and distribution were similar to normoxic perfused hearts. Furthermore, attenuation of intracellular edema with hyperosmotic buffer reduced cell death. Conclusions: We devised a method to determine edema and tissue water distribution. This method allowed us to demonstrate a role of edema in reperfusion‐induced cell death and could serve as a basis for the study of myocardial water distribution using magnetic resonance imaging.